2014
DOI: 10.1111/ctr.12398
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of endothelial dysfunction in Asian Indian patients with chronic kidney disease and changes following renal transplantation

Abstract: Patients with CKD have endothelial dysfunction as evidenced by reduced FMD. Decreased FMD indicating worsening endothelial function was noted with increasing severity of CKD. Within three months of RT, there was significant improvement in FMD, while NMD values did not change.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 44 publications
0
21
1
Order By: Relevance
“…Baseline transferrin was associated with changes in cf-PWV while baseline phosphate was associated with changes in CCA-IMT. CKD patients exhibit endothelial dysfunction as measured by FMD [3,5]. In previous studies, transplantation has been shown to improve FMD, acutely and at 12 months [14,15].…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…Baseline transferrin was associated with changes in cf-PWV while baseline phosphate was associated with changes in CCA-IMT. CKD patients exhibit endothelial dysfunction as measured by FMD [3,5]. In previous studies, transplantation has been shown to improve FMD, acutely and at 12 months [14,15].…”
Section: Discussionmentioning
confidence: 95%
“…This recovery may be due to improvements in traditional and uraemia-related non-traditional risk factors [6]. Despite this, FMD values were often still lower compared to controls [5,6].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations